Russian gas, Ukrainian pipelines, and European supply security: Lessons of the 2009 controversies - Kirsten Westphal (Stiftung Wissenschaft und Politik (SWP), 2009)
The Russian-Ukrainian gas controversy of January 2009 provoked the until then biggest gas supply crisis in Europe. At the same time, it marked a turning-point in the relationship between Russia, Ukraine and the European Union. The controversy clearly demonstrated that the recurrent confrontations between Russia and Ukraine have deep structural roots that jeopardize security on Europe's most important transit route. Although both countries concluded a new gas agreement in January 2009, this by no means signifies that all conflicts have now been settled. There is still the incessant political and economic crisis in Ukraine which is closely intertwined with severe problems in the country's energy sector. Russia and the EU, in turn, may have strategic interests in the Ukrainian energy market and its future orientation but their relationship is characterized by latent competition. The smouldering conflicts confront Germany and the EU with challenges on energy policy and, more broadly, on foreign policy whose urgency is connected with specific conditions of geography and infrastructure: The EU is the world's biggest net importer of gas; Russia is the biggest gas producer and exporter as well as the country with the biggest proven gas reserves; and Ukraine is by far the most important transit country for Europe. These facts of life will remain unchanged in the foreseeable future. Gas imports from the East, therefore, will remain a constant irritant and testing ground for a common European energy policy. These interconnections pose the question as to the lessons and consequences that should be drawn for German and European policy
Keywords: 320